Agile Anywhere Essays on Agile Projects and Beyond - Hazzan, Orit.; Dubinsky, Yael.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
The message conveyed in this work is that agility can be implemented anywhere. Accordingly, ten guidelines are presented for the adoption of agility to enable us to cope with changes in our lives, in our teams, and in our organizations. Since the authors advocate agility, the content is presented in the form of concise standalone chapters, allowing the reader to focus on the specific topic they wish to adopt in order to become agile.
Introduction to Agile Anywhere -- From 1st to 2nd Edition -- The Agile Manifesto -- Change -- Team -- Customers and Users -- Time Measures -- Quality -- Learning -- Abstraction -- Trust -- Globalization -- Reflection.
Keywords: Software engineering; Project management; Software Engineering; Project Management